Epidemiological analysis of adverse pregnancy events and associated risk factors in the border area of Guangzhou and Foshan, China - Wei Kong; Qingju Huang; Peixi Wang (Critical Public Health)
To investigate the incidence and influencing factors of adverse pregnancy events (APEs) among pregnant women in the urban-rural fringe areas of Guangzhou and Foshan, emphasizing public health significance in underserved Chinese border regions to develop targeted prevention strategies. A total of 3010 pregnant women who delivered in this region in 2019 were selected for this retrospective cross-sectional study. Demographic characteristics, pregnancy, and delivery information were collected through questionnaires and validated using medical records. Participants were divided into groups based on the occurrence of APEs. Binary logistic regression analysis was used to identify factors associated with APEs. Among the 3010 participants, 1797 (59.70%) experienced APEs. The incidence rates were 7.91% for pregnancy complications, 50.33% for pregnancy comorbidities, and 11.69% for fetal and adnexal abnormalities. The most common conditions detected were gestational diabetes (22.26%), thyroid disease (15.42%), anemia (9.60%), birth defects (4.65%), and viral hepatitis (3.32%). Binary logistic regression analysis revealed that Guangdong nativity (OR = 1.224, 95% CI: 1.033–1.450), rural residency (OR = 1.389, 95% CI: 1.024–1.884), urban health insurance (OR = 0.579, 95% CI: 0.452–0.742), New Rural Cooperative Medical Insurance (OR = 0.456, 95% CI: 0.359–0.581), age, pre-pregnancy BMI, tertiary hospital antenatal care (OR = 0.402, 95% CI: 0.337–0.479), male fetal sex (OR = 1.569, 95% CI: 1.242–1.982), and cesarean delivery (OR = 2.259, 95% CI: 1.695–3.009) were significant factors influencing APEs. High APEs incidence, particularly pregnancy comorbidities, exists among Guangzhou-Foshan border pregnant women. Promoting standardized antenatal care, early detection, and timely intervention is crucial to reduce APEs and enhance maternal/offspring health short- and long-term.